Rancang Bangun Sistem Pemantau Ketinggian dan Kecepatan Arus Air serta Perekam Kondisi Sungai Berbasis Android - Abd. Wahid Al Anas (Politeknik Negeri Malang, 2017)
Now a days, the condition of the river has been contaminated by householdwaste especially in the urban areas, the waste comes from people who are not responsible for the trash,so it potentially causes floods. Therefore, this research aims to design a system to monitor water level height and water speed as well as river condition recorder based on android. The use of ultrasonic sensor as an indicator to find out high levels of surface water, the optocoupler sensor as an indicator to know the speed of the water flow and IP cameras as a tool of monitoring the condition of the river are actual and direct. Research on the design of the ultrasonic sensor and optocoupler sensor resulted in average percentage error of measurement of 0.54% and 9.35%. IP camera that was designed as a visualization tool monitoring the condition of the river was able to produce on average the smallest delay 0ms. The notification system was implemented on the device users generating the biggest delay on average 22,9s and an average delay of the smallest 9,6s. QoS analysis on android gained the biggest delay of 1.64ms, the largest throughput of 81.01 Kb/s and packet loss of 0%. While QoS analysis on the website obtained the biggest delay of 58ms, the largest throughput of 19.3 KB/s and packet loss of 0%.